Pay more, earn less, work harder-new evidence on foreign subsidiary performance and market efficiency in emerging markets - Camilla Jensen (Center for Social and Economic Research (CASE), 2009)
Foreign subsidiary performance and market efficiency effects are estimated and confronted in this paper using a rich firm-level panel for Polish manufacturing. Besides estimating total factor productivity, other performance measures are calculated and contrasted such as labor productivity, employment growth, markup levels and profitability. The findings show that foreign subsidiaries in Poland pay more (in wages and capital), earn less (in terms of profitability or ROA) and work harder (in terms of TFP and labor productivity) relative to their domestic counterparts. Foreign subsidiaries contribute with higher employment growth than other domestic and new firms. There is no evidence that foreign subsidiaries have significantly reduced market efficiency within the period of study and across the industries and entry modes investigated on average. Controlling for competition (which is found to have a negative effect on efficiency) the paper documents significant intra-industry spillovers. The effect is estimated to be twice as high within the foreign owned industrial communities as compared to the cross effect to domestic firms.
Keywords: F23; L25; O14; O33; 330; multinational firms; economic growth; firm performance; spillovers; Ausländische Tochtergesellschaft; Multinationales Unternehmen; Auslandsinvestition; Unternehmenserfolg; Spillover-Effekt; Schätzung; Polen